The Influence of Digital Literacy and Digital Capability on Personal Innovativeness on Final Year Student of Telkom University - Hanifa Philanthropist Hamid; Kiki Sudiana Kiki Sudiana (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Telkom University has hopes for its graduates to be able to create a culture of research and innovation that is useful in improving the quality of life of the community. Efforts to realize these expectations are needed digital literacy and  digital capability as a foundation and provision in thinking, learning, communicating, working together, and working that will later foster personal innovativeness. The purpose of this study was to see how big the condition of digital literacy, digital capability, and personal innovativeness and how the influence of digital literacy and digital capability on personal innovativeness in Telkom University graduate students. The study used quantitative methods with questionnaires as data retrieval as many as 377 respondents. The respondents involved were telkom university's final-level students. The questionnaire in the study had 36 statements with a five-point likert scale measurement. The sampling method used is probability with the proptionate stratified random sampling technique. The results of this study are explained through data analysis techniques in the form of descriptive analysis, multiple linear regression, hypothesis tests, and coefficients of determination. The results obtained from this study indicate that digital literacy has a significant positive effect on personal innovation and digital ability has a significant positive effect on personal innovation. The coefficient of determination test shows that digital literacy and digital ability variables have an influence of 35.8% on personal innovation, while the other 64.2% is influenced by other variables.